The Importance of the International Criminal Police Organization in The Field of Combating Terrorism and Its Role in Developing the Rules of International Criminal Law (Al-Mukhtar Journal of Legal Science, 2024)
The crime of transnational terrorism has become a complex and multi-ideological phenomenon, due to various factors, and the methods of committing it have evolved. Although its methods were traditional and caused limited casualties among the targeted groups, they have evolved. It is carried out with extreme precision, taking advantage of information destruction technologies using international communications networks. The loss of life and property in regular wars is almost comparable to these losses, as well as the dangers associated with the use of chemical and biological weapons by extremist groups. occupy an important place in the world. On the international scene, particularly after the collapse of many Arab countries following the geopolitical events of 2011, fears emerged that the arsenal of weapons left behind by these countries would be exploited to carry out terrorist operations, forcing countries to make efforts to reduce this crime.
Keywords: International criminal police organization; international terrorism; organized crime; international justice; bulletins